2001
DOI: 10.1074/jbc.m010472200
|View full text |Cite
|
Sign up to set email alerts
|

The Unique Cyanobacterial Protein OpcA Is an Allosteric Effector of Glucose-6-phosphate Dehydrogenase in Nostoc punctiformeATCC 29133

Abstract: Glucose-6-phosphate dehydrogenase (G6PD), encoded by zwf, is essential for nitrogen fixation and dark heterotrophic growth of the cyanobacterium Nostoc punctiforme ATCC 29133. In N. punctiforme, zwf is part of a four-gene operon transcribed in the order fbp-tal-zwfopcA. Genetic analyses indicated that opcA is required for G6PD activity. To define the role of opcA, the synthesis, aggregation state, and activity of G6PD in N. punctiforme strains expressing different amounts of G6PD and/or OpcA were examined. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 26 publications
3
50
0
Order By: Relevance
“…OpcA has been shown to acts as an allosteric activator of Glucose-6-Phosphate dehydrogenase (G6PD) in Nostoc punctiforme, which is an essential enzyme for nitrogen fixation and dark heterotrophic growth. 12 Being OpcA an allosteric activator, it could be hypothesized that OpcA also activates the molecule responsible of proliferating HIP1. However, a spurious association between OpcA and HIP1 abundance can't be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…OpcA has been shown to acts as an allosteric activator of Glucose-6-Phosphate dehydrogenase (G6PD) in Nostoc punctiforme, which is an essential enzyme for nitrogen fixation and dark heterotrophic growth. 12 Being OpcA an allosteric activator, it could be hypothesized that OpcA also activates the molecule responsible of proliferating HIP1. However, a spurious association between OpcA and HIP1 abundance can't be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…1). The oxidative pentose phosphate (OPP) pathway enzyme 6-phosphogluconate dehydrogenase (6PGD, Sp25) was highly abundant, while glucose-6-phosphate dehydrogenase (G6PD) (Summers et al, 1995;Hagen & Meeks, 2001) was not identified. The latter finding corroborates earlier data showing that light inhibits the activity of G6PD in Anabaena sp.…”
Section: Discussionmentioning
confidence: 99%
“…7A) (Supplementary file S6), including OpcA, the unique cyanobacterial Zwf activator (Hagen and Meeks 2001). In contrast, only two of the 6 KGs listed for NADP(H)-metabolism were retained by the script (Fig.…”
Section: Case Study 2 -Nadp(h)-metabolismmentioning
confidence: 99%
“…PCC 7424, and links to Zwf via slr1793 (talu) and slr1734. The latter gene is a homolog of OpcA, an allosteric regulator and activation factor of Zwf in other cyanobacteria (Hagen and Meeks 2001).…”
Section: Case Study 2 -Nadp(h)-metabolismmentioning
confidence: 99%
See 1 more Smart Citation